Clave de los géneros de moluscos terrestres mexicanos usando caracteres conquiológicos - Fahy, Neil E. (2003)
A total of 13 shell characteristics keys are presented, allowing identification of the 117 terrestrial mollusc genera that have been reported for Mexico.